Bridging the Gap Between Theory and Practice - Roy H.M. Sembel (Universitas Pelita Harapan, 2015)
Some concerns in the field of Business Management regarding the gap between theory and practice have been raised by practitioners and academicians. This keynote speech describes some lessons learned from the academic literature regarding this gap (whether the gap really exists, and if it exists, whether it needs to be bridged or closed, and how to bridge or close this gap), and shares the author's personal and professional experiences of living as both an academician and a practitioner. The main findings of this article are: (1) Yes the gap exists, however, it has to be viewed in a wider perspective to really understand the situation; (2) The gap in a specific area is bad and should become our concern, but in other areas it should not; (3) There are some ways to bridge or close the negative gap; (4) There exists hybrid career opportunities to become professionals that work both as an academician and a practitioner; (5) This new breed of hybrid professionals has a huge potential to bridge the bad theory-practice gap.